2017
DOI: 10.5210/ojphi.v9i2.8001
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging public health's participation in a Health Information Exchange to improve communicable disease reporting

Abstract: BackgroundInfectious diseases can appear and spread rapidly. Timely information about disease patterns and trends allows public health agencies to quickly investigate and efficiently contain those diseases. But disease case reporting to public health has traditionally been paper-based, resulting in somewhat slow, burdensome processes. Fortunately, the expanding use of electronic health records and health information exchanges has created opportunities for more rapid, complete, and easily managed case reporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…Initiatives to standardize and automate case report form completion have been developed (23) and piloted (24), which have shown promise at reducing the time to complete reporting. Similar to our results, others have found that health information exchanges show value in prepopulating key elements for reporting through automated matching and searches in the patient record(25). The use of FHIR(26) may provide a viable path for automatic of public health case reporting and reduce administrative burden: when combined with an ELR based trigger for a case (in this example, sexually transmitted infection cases), an app that executed a FHIR-based query could complete an electronic case report form in 85% of cases(21).…”
Section: Discussionsupporting
confidence: 90%
“…Initiatives to standardize and automate case report form completion have been developed (23) and piloted (24), which have shown promise at reducing the time to complete reporting. Similar to our results, others have found that health information exchanges show value in prepopulating key elements for reporting through automated matching and searches in the patient record(25). The use of FHIR(26) may provide a viable path for automatic of public health case reporting and reduce administrative burden: when combined with an ELR based trigger for a case (in this example, sexually transmitted infection cases), an app that executed a FHIR-based query could complete an electronic case report form in 85% of cases(21).…”
Section: Discussionsupporting
confidence: 90%
“…One encouraging area of improvement in public health surveillance has been the adoption of an algorithm to automatically fill in all of the fields of the reportable disease forms directly from data available in the EHR 37 . These “auto filled” forms reduced the reporting burden on clinicians, decreased the time of the initial report by 2.7 days, and reduced the time to close a case by 0.2 day.…”
Section: Resultsmentioning
confidence: 99%
“…Studies in other countries have shown the use of prepopulated forms was found to decrease the time needed to begin documenting and closing case investigations 44. In addition, different approaches have also attempted to improve reporting of notifiable diseases.…”
Section: Discussionmentioning
confidence: 99%